Pandangan Dunia Akutagawa dalam Kappa - Dyah Ekawati Eriolita; Sri Oemiati (Fakultas Ilmu Budaya, Universitas Dian Nuswantoro, 2019)
Akutagawa Ryuunosuke is a great author who lived during the Taishoo era (1912-1926). According to Akutagawa, every author must have a worldly instinct as an absolute impulse of wisdom. If an artist has lost his worldly instincts, it means he has ended himself as an artist. There are two ways left, being crazy or die. Worldly instincts are meant by human desire especially for food and sex. Before Akutagawa died, he had a chance to create a very famous literary work, Kappa (1927) which tell a situation between dreams and reality. Akutagawa indirectly wanted to convey what he felt in his life through one of his works, Kappa. In this study the author uses a genetic structuralism approach that emphasizes on the synchronic meaning. It is the meaning which concernes with events in a limited period. The aim of this study was to find out Akutagawa's world views on Japanese society in the Taishoo era, towards the Ie system, religion and women. Â Kata kunci: world views, genetic structuralism, Kappa.